Relationships between teacher’s instructional strategies and their knowledge: A study of seventh-grade mathematics teachers - Masduki, Masduki; Suwarsono, Suwarsono; Teguh Budiarto, Mega (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2023)
Many studies showed that teachers' knowledge of instructional strategies is related to another component of pedagogical content knowledge. However, studies on teachers' reasons for choosing their instructional strategies still need to be reported. Three mathematics teachers were investigated using a case study research design. The data were gathered through two semi-structured interviews, pre- and post-observation, as well as observations. Pre-observation interviews explored teacher's knowledge of instructional strategies (KIS) based on their experiences or knowledge. Meanwhile, the post-interview investigated teachers' reasons for choosing instructional strategies based on the observations. Five to ten lesson hours were allocated to observe the teachers' activities in learning on the topic of linear equations and inequalities of one variable. A cross-case analysis was performed to compare the teachers' KIS and their reasons for choosing instructional strategies in teaching practice. The findings showed that lecturing, questioning, and solving problems are the most dominant strategies used by teachers. Only one teacher used group discussion in her teaching activities. The finding also indicates that the knowledge of the student's understanding, curriculum, beliefs, and teaching context are factors that influence teachers in choosing instructional strategies. In addition, the reasons for choosing those strategies are varied.